Penerapan Budaya Kerja dalam Meningkatkan Kinerja Pegawai pada PT. PLN (Persero) Uip Sumbagteng di Pekanbaru Riau - Muhammad Renaldo; Sehani Sehani (Yayasan Almanar Pujud, 2026)
This study aims to determine how the implementation of work culture improves employee performance and identify obstacles faced by PT PLN (Persero) UIP Sumbagteng in Pekanbaru, Riau. The implemented work culture is based on the AKHLAK values ​​(Trustworthy, Competent, Harmonious, Loyal, Adaptive, and Collaborative) as work guidelines for all employees. This study shows that the implementation of the AKHLAK work culture contributes positively to improving discipline, responsibility, team collaboration, and employee performance. However, there are obstacles such as resistance from senior employees to digitalization, inconsistency in the implementation of SOPs between units, and minimal feedback from leaders. The company is advised to strengthen the socialization of work culture values, increase technology training, and improve communication systems and performance assessments.